Up-glacier propagation of surface lowering of Yala Glacier, Langtang Valley, Nepal Himalaya - Sojiro Sunako; Koji Fujita; Takeki Izumi; Satoru Yamaguchi; Akiko Sakai; Rijan Bhakta Kayastha (Journal of Glaciology, 2023)
We quantify the surface elevation changes along Yala Glacier in Langtang Valley, Nepal Himalaya, since 1981 using geodetic methods to understand the recent evolution and current state of small debris-free glaciers across the region. We analyse differential global positioning system measurements and aerial stereo imagery that were acquired along Yala Glacier in 2007, 2009, 2012 and 2015 to generate digital elevation models for each calculation period. Continuous surface lowering has mainly been observed across the down-glacier area during the calculation periods, although a large degree of variability exists, with this lowering trend propagating up-glacier in recent years. The area-weighted glacier mass balances range from −0.98 ± 0.27 to −0.26 ± 0.30 m w.e. a−1 for the five calculation periods (1981–2007, 2007–2009, 2009–2012, 2012–2015 and 2007–2015). These calculated mass-balance data reveal that Yala Glacier has undergone accelerated mass loss since the late 2000s, which is consistent with the results of previous in situ measurement and remote-sensing studies.